Impact of Foreign Direct Investment, Productivity, and Growth on Indonesian Youth Unemployment - Annisa Rahma Febriyanti; Sulistya Rusgianto; Sri Herianingrum; Dian Ghani Reza Dasangga (Jurnal Ekonomi Pembangunan, 2024)
Unemployment is a consistent economic challenge faced by all countries. Indonesia, as a developing country, grapples with unemployment issues predominantly affecting young individuals. This research aims to examine the impact of Foreign Direct Investment (FDI), economic growth, and labor productivity on youth unemployment in Indonesia. Annual time series data from 1991 to 2022 were analyzed using Autoregressive Distributed Lag (ARDL) technique. The study reveals a significant negative relationship between economic growth and labor productivity with youth unemployment in the long term. Meanwhile, in the short term, FDI and labor productivity have a significant positive impact on youth unemployment. It is hoped that the Indonesia government will prioritize the creation of job opportunities for young domestic workers and provide training to enhance the quality of youth workforce in Indonesia